(untitled) (Ustozlar uchun, 2025)
This article discusses the structure of EFL classes and highlights the importance of organizing English lessons effectively. It explains the main stages of a lesson, including warm-up, presentation, practice, production, and feedback. The article shows how a clear lesson structure helps students improve language skills, increase motivation, and gain confidence in using English. It also emphasizes the role of the teacher in guiding and supporting learners throughout the lesson.